COMPARATIVE CHARACTERISTICS OF ALEN, M. MONTESORI AND S. FRENE’s PEDAGOGICAL CONCEPTS - Martianova, Mariia (Educological discourse, 2018)
The article examines the main pedagogical concepts of the 20th century, the authors of which are scientists M. Montessori, S. Frenne and Alain (Emile-Auguste Chartier). Their main aim was to find pedagogical ways to improve the educational system and bring up new generation which was capable to face new life demands. The child should not be a reservoir of knowledge, but he had to be educated as a thinking creature that combines intelligence, creativity and subconscious. Three scholars had the main humanistic ideas of learning that would allow a child to develop his natural properties and opportunities. They agreed that the first step in acquiring the necessary skills was developing of self-discipline. Despite following the main vector for learning, scientists used different educational methods and approaches. The main components which should be presented in teacher, according to M. Montessori are the ability to create comfortable and creative environment; to communicate with the students and to observe their work. The main elements of the pedagogical model by S. Frene, which stimulate the students’ interest in learning, are analyzed. The most famous examples are free text methods, educational cards, school printing and magazines which, according to the educator, can grow students’ interest, as curiosity is the best encouragement for learning. The idea of Alain’s educational double function, which consists of preparing for the present and future difficulties, is observed. Having compared the scholar’s pedagogical concepts, we have emphasized the basic principles of teaching, which are used nowadays. They are the principles of freedom and discipline, the principle of mentoring, the principle of favorable environment and the principle of working capacity.